An overview of using qualitative techniques to explore and define estimates of clinically important change on clinical outcome assessments - Hannah Staunton; Tom Willgoss; Linda Nelsen; Claire Burbridge; Kate Sully; Diana Rofail; Rob Arbuckle (SpringerOpen, 2019)
Abstract Establishing meaningful change thresholds for Clinical Outcome Assessments (COA) is critical for score interpretation. While anchor- and distribution-based statistical methods are well-established, qualitative approaches are less frequently used. This commentary summarizes and expands on a symposium presented at the International Society for Quality of Life Research (ISOQOL) 2017 annual conference, which provided an overview of qualitative methods that can be used to support understanding of meaningful change thresholds on COAs. Further published literature and additional examples from multiple disease areas which have also qualitatively explored the concept of meaningful change are presented. Semi-structured interviews conducted independently from a clinical trial, exit interviews conducted in the context of a clinical trial, focus groups, vignettes and the Delphi panel method can be used to obtain data regarding meaningful change thresholds, with advantages and disadvantages to each method. Semi-structured interviews using concept elicitation (CE) or cognitive debriefing (CD) methods conducted independently from a clinical trial can be an efficient way to gain in-depth patient/caregiver insights. However, there can be challenges with reconciling heterogeneous data across diverse samples and in interpreting the qualitative insights in the context of quantitative score changes. Semi-structured qualitative interviews using CE/CD methods embedded as exit interviews in a clinical trial context with patients/caregivers can provide insights which can augment quantitative findings based on analysis of clinical trial data. However, there are logistical challenges relating to embedding the interviews in a clinical trial. Focus groups and the Delphi panel method can be valuable for reaching consensus regarding meaningful change thresholds; however, for face-to-face interactions, social desirability bias can affect responses. Finally, using vignettes and taking a mixed methods approach can aid in achieving consensus on the minimum score change endorsed by respondents as a meaningful improvement/decrement. However, the approach can be cognitively challenging for participants and reaching a consensus is not guaranteed. Anchor- and distribution- based methods remain critical in establishing responder definitions. Nonetheless, qualitative data has the potential to provide complementary support that a certain level of change on the target COA, which has been statistically supported, is truly important and meaningful for the target population.